White mothers of Black biracial children: mixed race as the new Mulatto - Bell, Erin Halcyon, author; Bubar, Roe, advisor; Souza, Caridad, committee member; Jacobi, Tobi, committee member (Colorado State University. Libraries, 2016)
This research explores how White women perceive their roles as parents to "mixed" race or biracial Black children. This qualitative project analyzes data from in person interviews, photographs and comments posted on Internet blogs, Facebook fan pages of mixed race children. Core elements of grounded theory are used as methodology to explore how White women understand themselves in relation to the role they play in pursuing their desire to create a mixed race or biracial child. Emerging themes from this research include: Objectification of Mixed Race Children, "We are going to get designer babies!" Displacing Black Women, and "I have mixed kids, so I can't be racist."